Estimation of Cephalometric Norm for Bangladeshi Children (Steiners Method) (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2013)
Objective: The objective of this study was to establish cephalometric norms of Bangladeshi children age range (10-13years) and to compare it with accepted standards for the Caucasian population according to Steiner analysis. Methods: Fifty healthy Bangladeshi children both male and female, with a mean age of 12.3 years, were selected from different schools of Dhaka. Selection was made on the basis of normal occlusion, balanced and pleasing profile with no obvious facial asymmetry. None of the children have undergone orthodontic treatment prior to this study. Lateral skull cephalograms were taken and traced using a standardized technique. Each cephalogram was traced twice with a one week interval by the authors. All angular and linear measurements were calculated to the nearest 0.5 degree and 0.5 mm, respectively. Steiner's method of cephalometric analysis was used to establish cephalometric norms. Results: A comparison of the results with the Steiner standards showed that the Bangladeshi children were more protrusive skeletally and dentally with a greater tendency towards bimaxillary protrusion. Further, there was a decrease in the lower facial height. Conclusion: The results of the study support the fact that norms and standards of one racial group could not be used without modification for other racial group and each different racial group would have to be treated according to its individual characteristics. DOI: http://dx.doi.org/10.3329/bjodfo.v1i1.15970 Ban J Orthod & Dentofac Orthop, October 2010; Vol-1, No.1, 1-4